Uncertainties in Monte Carlo-based absorbed dose calculations for an experimental benchmark. (21st September 2015) - Renner, F; Wulff, J; Kapsch, R-P; Zink, K
Abstract: There is a need to verify the accuracy of general purpose Monte Carlo codes like EGSnrc, which are commonly employed for investigations of dosimetric problems in radiation therapy. A number of experimental benchmarks have been published to compare calculated values of absorbed dose to experimentally determined values. However, there is a lack of absolute benchmarks, i.e. benchmarks without involved normalization which may cause some quantities to be cancelled. Therefore, at the Physikalisch-Technische Bundesanstalt a benchmark experiment was performed, which aimed at the absolute verification of radiation transport calculations for dosimetry in radiation therapy. A thimble-type ionization chamber in a solid phantom was irradiated by high-energy bremsstrahlung and the mean absorbed dose in the sensitive volume was measured per incident electron of the target. The characteristics of the accelerator and experimental setup were precisely determined and the results of a corresponding Monte Carlo simulation with EGSnrc are presented within this study. For a meaningful comparison, an analysis of the uncertainty of the Monte Carlo simulation is necessary. In this study uncertainties with regard to the simulation geometry, the radiation source, transport options of the Monte Carlo code and specific interaction cross sections are investigated, applying the general methodology of the Guide to the expression of uncertainty in measurement. Besides studying the general influence of changes in transport options of the EGSnrc code, uncertainties are analyzed by estimating the sensitivity coefficients of various input quantities in a first step. Secondly, standard uncertainties are assigned to each quantity which are known from the experiment, e.g. uncertainties for geometric dimensions. Data for more fundamental quantities such as photon cross sections and the I -value of electron stopping powers are taken from literature. The significant uncertainty contributions are identified as the energy of the radiation source and the underlying photon cross sections as well as the I -value of media involved in the simulation. The combined standard uncertainty of the Monte Carlo calculation yields 0.78% as a conservative estimation. The result of the calculation is close to the experimental result and with each combined standard uncertainty <1%, the accuracy of EGSnrc is confirmed. The setup and methodology of this study can be employed to benchmark other Monte Carlo codes for the calculation of absorbed dose in radiotherapy.